Association between phosphate disturbances and mortality among critically ill patients with sepsis or septic shock - Al Harbi, Shmeylan A. (BMC Pharmacol Toxicol, 2021)
OBJECTIVE: The aim of this study is to examine the association of hypophosphatemia and hyperphosphatemia on the first day of ICU admission with mortality in septic critically ill patients. METHODS: In this retrospective cohort study, all adult patients who were admitted to the medical-surgical ICUs between 2014 and 2017 with sepsis or septic shock were categorized as having hypophosphatemia, normophosphatemia and hyperphosphatemia based on day 1 serum phosphate values. We compared the clinical characteristics and outcomes between the three groups. We used multivariate analysis to examine the association of hypophosphatemia and hyperphosphatemia with these outcomes. RESULTS: Of the 1422 patients enrolled in the study, 188 (13%) had hypophosphatemia, 865 (61%) normophosphatemia and 369 (26%) had hyperphosphatemia. The patients in the hyperphosphatemia group had significantly lower GCS, higher APACHE II scores, higher serum creatinine, increased use of vasopressors, and required more mechanical ventilation with lower PaO2/FiO2 ratio compared with the other two groups. In addition, the hyperphosphatemia group showed significantly higher ICU and hospital mortality in comparison with the other two groups. CONCLUSION: Hyperphosphatemia and not hypophosphatemia on the first ICU admission day was associated with an increase in the ICU and hospital mortality in septic critically ill patients.